Trauma Recovery Program: Community-Based Positive Psychotherapy Assistance for Victims of Violence in Lampung - Sulastri, Sulastri; Nurulia, Eki Tiyas; Khairani, Khairani; Warsiyah, Warsiyah (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2026)
Violence against women and children is an urgent social issue that has a multidimensional impact, both psychologically, socially, and economically. East Lampung Regency recorded a significant increase in cases of violence, especially in the household, with victims generally experiencing long-term trauma and loss of economic independence. This community service aims to assist victims of violence through an integrative approach that includes spiritual-based positive psychotherapy, entrepreneurial training, and the formation of advocacy-based recovery communities. The partners in this activity are the East Lampung Women's Empowerment and Child Protection Office (DP3AP2KB) and the victims of violence who have been identified. The service method is carried out through six stages: socialization, psychological training, individual counseling, business training, public education, and evaluation. The results showed a significant improvement in the psychological well-being of the victims, with an increase in confidence scores, the ability to manage emotions, and optimism. Economically, more than 70% of participants managed to start small-scale household businesses after participating in training and mentoring. In addition, there has been a positive change in public perception of the issue of violence and support for victims. These findings suggest that a holistic approach that brings together psychological recovery and economic empowerment within the framework of community advocacy can be a model of effective and sustainable intervention. The results of this service are important as the basis for the development of similar programs in other regions, especially those with comparable geographical and social conditions